Effect of 6 Months of Erythromycin Treatment on Inflammatory Cells in Induced Sputum and Exacerbations in Chronic Obstructive Pulmonary Disease - He, Zhi-Yi; Ou, Li-Mei; Zhang, Jian-Quan; Bai, Jing; Liu, Guang-Nan; Li, Mei-Hua; Deng, Jing-Min; MacNee, William; Zhong, Xiao-Ning (Respiration, 2010)
Background: Chronic obstructive pulmonary disease (COPD) is characterized by airway inflammation and is associated with acute exacerbations. Macrolide antibiotics have been shown to exhibit anti-inflammatory effects in some chronic airway inflammatory diseases. Objective: The aim of this study was to assess the effect of treatment with erythromycin on airway inflammation and health outcome in COPD patients. Methods: We conducted a randomized, placebo-controlled, double-blind trial of erythromycin for a period of 6 months. Thirty-six COPD patients were randomized to treatment with oral erythromycin (125 mg, three times/day) or placebo. The primary outcomes were neutrophil number in sputum and exacerbations. Results: Thirty-one patients completed the study. At the end of treatment, neutrophil counts in the sputum were significantly decreased in the group treated with erythromycin compared with placebo-treated patients (p = 0.005). Total cells in the sputum and neutrophil elastase in sputum supernatant were also significantly decreased in those treated with erythromycin compared with the placebo group (p = 0.021 and p = 0.024, respectively). The mean exacerbation rate was lower in the erythromycin group than in the placebo group (relative risk = 0.554, p = 0.042). Kaplan-Meier survival analysis showed that erythromycin significantly delayed the time to the first COPD exacerbation compared with placebo (p = 0.032). Conclusions: Erythromycin treatment in COPD patients can reduce airway inflammation and decrease exacerbations and may therefore be useful in the management of COPD.